PEMANFAATAN TEKNOLOGI DALAM PEMBELAJARAN DARING BAHASA JEPANG BAGI SISWA KELAS XII SMKN 7 PEKANBARU - Viranda Anissa; Rifo Perdana Faizal; Yenny Aristia Nasution (Undiksha Press, 2022)
This study aims to describe the use of technology in the online learning process of Japanese subjects for class XII students of SMKN 7 Pekanbaru and to find out the obstacles experienced during the online learning process of Japanese subjects for class XII students of SMKN 7 Pekanbaru. The subjects in this study were 10 students of class XII of SMKN 7 Pekanbaru, while the object of this research was primary data in the form of interviews and secondary data in the form of documentation. This type of research is qualitative. Data collection techniques by means of observation, interviews, and documentation. The data analysis technique is descriptive and qualitative. The results of the study indicate that the use of technology can be a solution to the current pandemic situation and make online learning Japanese more varied through various applications so that students are not bored and understand the material presented faster and the obstacles faced in the online learning process due to signal and signal constraints. students who do not have smartphones in carrying out the learning process remotely.